2018
DOI: 10.3390/ijms19020496
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Inhibitor Induced Radiation Sensitization Effects on Human Cancer Cells after Photon and Hadron Radiation Exposure

Abstract: Suberoylanilide hydroxamic acid (SAHA) is a histone deacetylase inhibitor, which has been widely utilized throughout the cancer research field. SAHA-induced radiosensitization in normal human fibroblasts AG1522 and lung carcinoma cells A549 were evaluated with a combination of γ-rays, proton, and carbon ion exposure. Growth delay was observed in both cell lines during SAHA treatment; 2 μM SAHA treatment decreased clonogenicity and induced cell cycle block in G1 phase but 0.2 μM SAHA treatment did not show eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 56 publications
4
35
1
Order By: Relevance
“…Among these, the application of romidepsin and SAHA is already approved in clinical practice, demonstrating their relevance in therapeutic modalities [72]. Nevertheless, inducing chromatin relaxation by histone-hyperacetylation holds enormous relevance in the context of radiation enhancement as well, since irradiation-induced reactive electrons and the concomitantly generated free radicals can ultimately target the DNA and such ionization events produce DNA base damage, DNA single strand breaks and double strand breaks [33,73].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, the application of romidepsin and SAHA is already approved in clinical practice, demonstrating their relevance in therapeutic modalities [72]. Nevertheless, inducing chromatin relaxation by histone-hyperacetylation holds enormous relevance in the context of radiation enhancement as well, since irradiation-induced reactive electrons and the concomitantly generated free radicals can ultimately target the DNA and such ionization events produce DNA base damage, DNA single strand breaks and double strand breaks [33,73].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the novel nanoparticle radiosensitizers, many clinically used anti-cancer agents possess radiation enhancing activity. As an example, it has been shown that some histone deacetylase (HDAC) inhibitors like Vorinostat (also known as suberoylanilide hydroxamic acid, SAHA), applied in the clinical practice as a potent antineoplastic agent against different types of leukemia and solid tumors [32], might function effectively as radiosensitizer, broadening the spectrum of their utilization in different treatment modalities [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Another preclinical study in breast cancer cells MCF7, proved that a proper balance between HDACs and HATs is necessary to maintain the histone acetylation thereby the compaction of the chromatin to resist the development of resistant of cancer cells to radiation therapy [195]. So, an early diagnosis of tumor HDAC activity would increase the efficiency of HDAC/radiotherapy strategy of treating cancer cell [196]. Clinical trials.gov website showed only one such completed trials on brain metastases although not specifically arising from breast cancer metastasis (NCT00838929).…”
Section: Clinical Trialsmentioning
confidence: 99%
“…They found that valproic acid sensitized more hepatocellular carcinoma cells to proton than to photon irradiation, inducing prolonged proton-induced DNA damage and augmented proton-induced apoptosis. In addition, we recently reported that another HDACi, suberoylanilide hydroxamic acid (SAHA), successfully sensitized cancer cells to radiation, even with high LET radiation [18]. Importantly, we proved that SAHA selectively sensitized cancer cells to photon and particle radiation (Figure 1).…”
Section: Preclinical Analysis In Combination Therapy With Protonsmentioning
confidence: 63%